m6A and miRNA jointly regulate the development of breast muscles in duck embryonic stages - Gu, Lihong; Zhang, Shunjin; Li, Boling; Jiang, Qicheng; Xu, Tieshan; Huang, Yongzhen; Lin, Dajie; Xing, Manping; Huang, Lili; Zheng, Xinli; Wang, Feng; Chao, Zhe; et al. (Frontiers in Veterinary Science, 2022)
N6-methyladenosine (m6A) is an abundant internal mRNA modification and plays a crucial regulatory role in animal growth and development. In recent years, m6A modification has been found to play a key role in skeletal muscles. However, whether m6A modification contributes to embryonic breast muscle development of Pekin ducks has not been explored. To explore the role of m6A in embryonic breast muscle development of ducks, we performed m6A sequencing and miRNA sequencing for the breast muscle of duck embryos on the 19th (E19) and 27th (E27) days. A total of 12,717 m6A peaks were identified at E19, representing a total of 7,438 gene transcripts. A total of 14,703 m6A peaks were identified, which overlapped with the transcripts of 7,753 genes at E27. Comparing E19 and E27, we identified 2,347 differential m6A peaks, which overlapped with 1,605 m6A-modified genes (MMGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that MMGs were enriched in multiple muscle- or fat-related pathways, which was also revealed from our analysis of differentially expressed genes (DEGs). Conjoint analysis of m6A-seq and RNA-seq data showed that pathways related to β-oxidation of fatty acids and skeletal muscle development were significantly enriched, suggesting that m6A modification is involved in the regulation of fat deposition and skeletal muscle development. There were 90 upregulated and 102 downregulated miRNAs identified between the E19 and E27 stages. Through overlapping analysis of genes shared by MMGs and DEGs and the targets of differentially expressed miRNAs (DEMs), we identified six m6A-mRNA-regulated miRNAs. Finally, we found that m6A modification can regulate fat deposition and skeletal muscle development. In conclusion, our results suggest that m6A modification is a key regulator for embryonic breast muscle development and fat deposition of ducks by affecting expressions of mRNAs and miRNAs. This is the first study to comprehensively characterize the m6A patterns in the duck transcriptome. These data provide a solid basis for future work aimed at determining the potential functional roles of m6A modification in adipose deposition and muscle growth.